Spatial manifestation of resonant ionospheric signatures during the 11 March 2011 Tohoku-Oki earthquake - Nayak, Srinivas; Bagiya, Mala S.; Sunil, A.S. (My University, 2022)
Resonant coupling between the solid Earth and atmosphere leads to higher amplitudes of normal mode oscillations at ∼ 3.7 mHz and ∼4.4 mHz frequencies. Earthquake is one of the potential solid earth sources which can trigger the terrestrial resonant coupling. The present study addresses the resonant ionospheric signatures during the Mw 9.1 11 March 2011 Tohoku-Oki Earthquake (Tohoku EQ). The Tohoku EQ ruptured off the eastern coast of Northern Honshu along a major 200 km fault. We aim to characterise the spatial manifestation of resonant ionospheric signatures following the Tohoku EQ event. Our analysis demonstrates significant north–south asymmetry in spatial distribution of the resonant signatures encompassing the epicentre. This anisotropic behaviour has been scrutinised by referring to seismic and non-seismic parameters. The non-seismic parameters mainly of geomagnetic field-acoustic wave coupling and satellite observation geometry largely governed the ionospheric manifestations of seismic energy. This attempt elaborates the role of non- seismic parameters towards efficient understanding of the spatial manifestations of resonant ionospheric signatures during great earthquakes.
Keywords: Terrestrial resonance coupling during great earthquakes; Spatial manifestations of ionospheric resonant signatures; Role of non-seismic parameters in manifestations of resonant ionospheric signature; Mw 9.1 11 March 2011 Tohoku-Oki Earthquake; GEONET; Japan